Long term effects of inhaled corticosteroids in chronic obstructive pulmonary disease: a meta-analysis. Issue 1 (1st January 1999) - van Grunsven, P M; van Schayck, C P; Derenne, J P; Kerstjens, H A M; Renkema, T E J; Postma, D S; Similowski, T; Akkermans, R P; Jong, P C M Pasker-de; Dekhuijzen, P N R; van Herwaarden, C L A; van Weel, C
Abstract : BACKGROUND: The role of inhaled corticosteroids in the long term management of chronic obstructive pulmonary disease (COPD) is still unclear. A meta-analysis of the original data sets of the randomised controlled trials published thus far was therefore performed. The main question was: "Are inhaled corticosteroids able to slow down the decline in lung function (FEV1 ) in COPD?" METHODS: A Medline search of papers published between 1983 and 1996 was performed and three studies were selected, two of which were published in full and one in abstract form. Patients with "asthmatic features" were excluded from the original data. Ninety five of the original 140 patients treated with inhaled corticosteroids (81 with 1500 μg beclomethasone daily, six with 1600 μg budesonide daily, and eight with 800 μg beclomethasone daily) and 88 patients treated with placebo (of the initial 144 patients) were included in the analysis. The effect on FEV1 was assessed by a multiple repeated measurement technique in which points of time in the study and treatment effects (inhaled corticosteroids compared with placebo) were investigated. RESULTS: No baseline differences were observed (mean age 61 years, mean FEV1 45% predicted). The estimated two year difference in prebronchodilator FEV1 was +0.034 l/year (95% confidence interval (CI) 0.005 to 0.063) in the inhaled corticosteroid group compared with placebo. The postbronchodilator FEV1 showed a difference of +0.039 l/year (95% CI –0.006 to 0.084). No beneficial effect was observed on the exacerbation rate. Worsening of the disease was the reason for drop out in four patients in the treatment group compared with nine in the placebo group. In the treatment group six of the 95 subjects dropped out because of an adverse effect which may have been related to the treatment compared with two of the 88 patients in the placebo group. CONCLUSIONS: This meta-analysis in patients with clearly defined moderately severe COPD showed a beneficial course of FEV1 during two years of treatment with relatively high daily dosages of inhaled corticosteroids.